Effects of heat treatment on the structural, spectral, morphological, dielectric, and magnetic properties of Ba0.5Sr0.1Zn0.4Fe12O19 ferrite. Issue 17 (1st September 2021) - Shifa, Muhammad Shahzad; Khan, Waqar Ahmed; Albalawi, Hind; Al- Muhimeed, Tahani I.; AlObaid, Abeer A.; Mahmood, Q.; Khan, Muhammad Azhar; Gulbadan, Shagufta; Gilani, Zaheer Abbas; Qureshi, Imdadullah
Abstract: M-type Hexa-ferrites powders of chemical composition Ba0.5 Sr0.1 Zn0.4 Fe12 O19 was prepared by the use of the co-precipitation technique. The heat treatment of this ferrite composition was done at various temperatures (700, 800, 900, 1000, 1100, and 1200 °C) for 6 h. The X-ray diffraction (XRD) analysis of all the prepared powder samples confirmed the emergence of a hexagonal structure. The high-intensity peaks of the samples were indexed and showed a single phase. The size of crystallite was obtained within the range of 21–42 nm. The surface morphology was carried out with a Scanning electron microscope (SEM). The grain size showed the hexagonal shape, and average grain sizes were in the range of ~ 211 nm. Spectral information was found using the Fourier transform infrared (FTIR) spectroscopy to confirm the phase of M-type hexaferrite. The dielectric parameters were measured within the high-frequency range of 5 MHz - 3 GHz. The dielectric constant was increased with an increase in temperature. The dielectric studies were found by the establishment of space charge polarization as per the two-layer model provided by Maxwell-Wagner and the study of phenomena of Koop's theory. The magnetic characteristics including coercivity (HcB) and retentivity (Br) were measured from BH/JH hysteresis loops. The enhancement of coercivity was observed from 1.23 × 10 +3  Oe to 1.50 × 10 +3  Oe, while the retentivity increased from 1.334 × 10 +3  G to 1.598 × 10 +3  G with an increase in temperature. Outstanding properties of synthesized materials suggested their use in large-frequency applications, including recording media and permanent magnets.